Programmes of Educational Development 1961-66 (Third Plan) - Planning Commission, Government of India (Planning Commission, Government of India, 1961)
The Survey suggested that 47,992 middle schools would be needed in the country. These will serve a total of 7,48,098 habitations leaving 91,955 habitations without facilities of middle schools. In terms of percentage 89.1 of the total habitations would be served by middle schools and 10.9 would remain without such facilities.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Third Plan- Programmes of Educational Development